Pengaruh Kualitas Produk dan Harga Terhadap Keputusan Pembelian Sepeda Motor Yamaha pada PT. Alfa Scorpii - Praya, Ziekri R; Mubarak, Husni (SEIKO : Journal of Management & Business, 2024)
The purpose of this research is to find out whether there is an influence of product quality and price on the decision to purchase Yamaha motorbikes at PT. Alfa Scorpii at Sentral Yamaha Medan. The sample for this research was 82 consumers at PT. Alfa Scorpii Sentral Yamaha Medan in June 2024. The sample was taken using the accidental sampling method, that is, anyone who coincidentally meets the researcher can be used as a sample, if it is deemed that the person they accidentally met is suitable as a data source. Data analysis uses the Multiple Linear Regression test, while data processing uses SPSS. The research results show that partially product quality has an influence on purchasing decisions with the calculated t value being greater than the t table value, price also has a positive and significant effect on purchasing decisions with the calculated t value turning out to be greater than the t table value, while simultaneously product quality and price has a positive and significant effect on purchasing decisions with a calculated F value greater than F table.